Kiai Leadership Model in Developing the Culture of Memorizing the Qur'an - Gafur, Abdul; Baharuddin; Zuhriyah, Indah Amainatuz (Al-Hayat: Journal of Islamic Education, 2025)
This study aims to describe the leadership model of the Kiai in developing the culture of memorizing the Al-Qur'an at the Darul Fikri Islamic Boarding School in Sidoarjo Regency. A qualitative case study approach was used in this study. Data were collected through observation, in-depth interviews, and documentation. Inductive data analysis included categorizing data, grouping it into units of analysis, forming patterns, and drawing inductive conclusions based on the collected empirical data. Data Validity The researcher used source and method triangulation techniques and conducted reference adequacy. The study results indicate that the Kiai leadership applied is transformative, focusing on character building, strengthening spirituality, and achieving memorization targets systematically and measurably. The main strategies include arranging the students' daily schedules, time discipline, clear teaching methods, and leaders' active coaching involvement. The development of the tahfidz culture is supported by regular teacher development programs, student leadership training, and collaboration between teachers, parents, and boarding school administrators. The monitoring and evaluation process is carried out periodically with the tasmi' system, memorization tests, and digital technology for reporting students' progress. Furthermore, tahfidz teachers are required to possess high competence and moral-spiritual commitment, and are allowed to participate in a memorization program to recognise their achievements. The requirements for murajaah (recitation of the Qur'an) are also strictly regulated to maintain the quality of students' memorization, requiring students to recite without the Mushaf and repeat forgotten verses. These findings demonstrate that the success of a tahfidz culture is primarily determined by visionary leadership, collective involvement, and a structured and sustainable management system.